Estudo de preferência alimentar em pugilina morio (Linnaeus, 1758) (Molusca: Gastropoda: Melongenidae) - Nogueira, Igor Silva (2010)
The class gastropoda exhibits virtually all kinds of forage habits, among them: herbivorous, detritivore, suspensivore, carnivorous-predators, scavengers and parasites. The gastropodo Pugilina morio belongs to the family Melongenidae. This family has representatives that occur in almost every tropical and temperate seas. P. morio is the only species of Melongenidae represented in Brazil, presenting thick populations in some regions of the country, inhabiting estuarine zones, being an efficient bivalves predator. Very little is known about the forage preferences of P. morio and its predation strategies in function of the kind of the prey, so in this work we tried to make a study of its forage strategies, determining the forage items that compose its diet, determining its forage preferences and analyzing its predation strategies. The prey species used in laboratory were composed of the bivalve molluscs Anomalocardia brasiliana, Crassostrea rhizophorae, Iphigenia brasiliana, being all of them recognized and consumed as preys, showing that P. morio could be a generalist predator. The reproduction period of P. morio goes from July to November and in this period the female species don’t feed or feed very little, being possible evidence this fact in laboratory conditions. It could be observed in the predator behavior of P. morio that the strategy used by itself was the suffocation of its preys using its foot or even using its shell to open or to break the valves of its preys sucking all the visceral mass of them.